2022
DOI: 10.24912/jk.v14i1.15425
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leadership Style in Local Government in the Development of Sustainable Micro Entrepreneurship

Abstract: Micro entrepreneurship in several districts and municipalities has been growing rapidly. The progress of this micro entrepreneurship can be achieved because of the efforts of the micro entrepreneurship and the strength of the entrepreneurs. Entrepreneurship needs a sustainable system so that the micro business can be stronger and more developed. The development of the micro entrepreneurship also depends on the role and the partiality of its local government which is influenced by the leadership style of the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In terms of productivity, it is also still not developing and stable. This is supported by the results of research by Meirobie et al (2022) on micro-businesses in Belitung Regency which showed that there were 12% of entrepreneur respondents who stated that they had not succeeded in their business, there were still fluctuations in terms of income or business performance, and a lack of business consistency and partiality received from stakeholders in the micro business sector.…”
mentioning
confidence: 67%
“…In terms of productivity, it is also still not developing and stable. This is supported by the results of research by Meirobie et al (2022) on micro-businesses in Belitung Regency which showed that there were 12% of entrepreneur respondents who stated that they had not succeeded in their business, there were still fluctuations in terms of income or business performance, and a lack of business consistency and partiality received from stakeholders in the micro business sector.…”
mentioning
confidence: 67%
“…Regulation of the Head of LAN Number 12 of 2013 concerning guidelines for the implementation of level III leadership education and training aims to form a bureaucratic leader who has a high ability in elaborating the vision and mission of agencies into agency programs and can lead their implementation (Makatita & Kartini, 2022). Meanwhile, the Regulation of the Head of LAN Number 20 of 2015 concerning guidelines for the implementation of level IV leadership education and training aims to form a bureaucratic leader who has a high ability in planning agency activities and leading their implementation (Meirobie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of the Head of LAN Number 12 of 2013 concerning guidelines for the implementation of level III leadership education and training aims to form a bureaucratic leader who has a high ability in elaborating the vision and mission of agencies into agency programs and can lead their implementation (Makatita & Kartini, 2022). Meanwhile, the Regulation of the Head of LAN Number 20 of 2015 concerning guidelines for the implementation of level IV leadership education and training aims to form a bureaucratic leader who has a high ability in planning agency activities and leading their implementation (Meirobie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%